2013
DOI: 10.1007/s10096-013-1947-0
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin inhibits Porphyromonas gingivalis growth, biofilm formation, gingivomucosal inflammatory cytokine secretion, and in vitro osteoclastogenesis

Abstract: The prevention and treatment of periodontitis requires not only the control of causative pathogens, especially Porphyromonas gingivalis, but also the regulation of inflammatory immune response. Investigating auxiliary drugs for periodontitis during conventional treatments is, thus, quite important. Capsaicin, an agonist for the vanilloid receptor subtype 1 (TRPV1), due to its bacteriostatic activity against Gram-negative bacteria and anti-inflammatory effects, appears to be a promising drug. In this work, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 44 publications
3
43
0
1
Order By: Relevance
“…In the study of Dima et al [10] the antimicrobial activity of capsaicin was proved by using disc diffusion sensitivity tests against three bacteria: Staphylococcus aureus, Salmonela, and Escherichia coli. Whereas Zhou et al [22], as was done in the present study, evaluated the antimicrobial activity of capsaicin against a periodontogenic bacteria, Porphyromonas gingivalis. However, they used the microdilution method and also demonstrated the inhibitory effect of a MIH of 1.6% and MBC of 6.4%.…”
Section: Graph 1 -Inhibition Zone Of Agregatibacter Actinomycetemcomimentioning
confidence: 85%
See 2 more Smart Citations
“…In the study of Dima et al [10] the antimicrobial activity of capsaicin was proved by using disc diffusion sensitivity tests against three bacteria: Staphylococcus aureus, Salmonela, and Escherichia coli. Whereas Zhou et al [22], as was done in the present study, evaluated the antimicrobial activity of capsaicin against a periodontogenic bacteria, Porphyromonas gingivalis. However, they used the microdilution method and also demonstrated the inhibitory effect of a MIH of 1.6% and MBC of 6.4%.…”
Section: Graph 1 -Inhibition Zone Of Agregatibacter Actinomycetemcomimentioning
confidence: 85%
“…It was possible to observe that inhibition of the growth of the bacterial species Agregatibacter actinomycetemcomitans was lower at the different concentrations if capsaicin when compared with 0.12% chlorhexidine. Other studies have demonstrated the antimicrobial activity of capsaicin against diverse types of organisms of the oral cavity [22,12]. However, Agregatibacter actinomycetemcomitans was not included among the strains analyzed in any of these studies, which makes it impossible to perform comparison of the results found in the present study.…”
Section: Graph 1 -Inhibition Zone Of Agregatibacter Actinomycetemcomimentioning
confidence: 89%
See 1 more Smart Citation
“…Recent studies revealed the antibiofilm effects of roselle calyx extract and capsaicin, which is the active compound of Capsicum plants (chili peppers) against P. gingivalis [107,108]. The latter also reduces the viability of pre-formed biofilms and has an inhibitory effects on both inflammatory cytokine secretion and in vitro osteoclastogenesis.…”
Section: Treatment Of P Gingivalis–related Infectionsmentioning
confidence: 99%
“…Those effects are mostly caused by capsaicin, the active ingredient contained in the fruit stem of capsicum frutescens L. Previous research used capsaicin topically showed that it can be used as a therapy to cure pain due to inflammation. 2 The capsaicin content of each varieties of chili in Bandung showed that green chili (capsicum frutescens L.) has the highest amount of capsaicin that is equal to 2.11%. 3 The capsaicin has currently been used as a study material to determine the mechanism of pain and in pharmacotherapy to treat several pain disorders.…”
mentioning
confidence: 99%